Running on Parallel Tracks? Analysing the Effects of Linking Labour Standards to International Trade (Jurnal Kemanusiaan, 2017)
The purpose of this paper is to review the arguments for and against the linking of labour standards with international trade agendas. Efforts in linking labour standards and trade negotiations in the Western Hemisphere and ASEAN region are highlighted. The study provides a survey of the arguments, both, advocating for and opposing against such linkages. Empirical evidences from past studies found that ratification of labour standards are not related to trade performances. The advocates of the linkage proposed that it would protect the rights of workers in developing countries, while, the opposing parties argued that it is a form of disguised protectionism for developed countries. This paper concludes that a paradigm shift is required to bring both international trade negotiations and labour standard practices together. Recommendations for future study are also provided.